2013
DOI: 10.1111/jbi.12149
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history influences the effects of water–energy dynamics on oak diversity in Asia

Abstract: Aim Water–energy dynamics are often correlated with geographical patterns of terrestrial plant richness. However, the relative importance of water and energy on species richness is still being debated. Some studies suggest a transition in the relative importance of water and energy along a latitudinal gradient, i.e. that water is the most important factor at low latitudes, whereas energy is the leading factor at high latitudes. The generality of this transition is yet to be established and is the focus of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 43 publications
2
30
0
1
Order By: Relevance
“…Our analyses evidenced the significant roles of geography and climate in shaping Q. spinosa genetic structure (Table 2). Similar to that revealed in previous studies highlighting the importance of water availability and temperature on oak species demography (Sardans & Penuelas, 2005; Yang et al, 2009; Xu et al, 2013), the present study showed the effect of precipitation (PC1) on Q. spinosa genetic divergence but failed to uncover the effect of temperature (PC2). However, at the lineage level, both temperature (BIO 4) and precipitation (BIO 18) influenced the divergence of CEC lineage (Table 2).…”
Section: Discussionsupporting
confidence: 87%
“…Our analyses evidenced the significant roles of geography and climate in shaping Q. spinosa genetic structure (Table 2). Similar to that revealed in previous studies highlighting the importance of water availability and temperature on oak species demography (Sardans & Penuelas, 2005; Yang et al, 2009; Xu et al, 2013), the present study showed the effect of precipitation (PC1) on Q. spinosa genetic divergence but failed to uncover the effect of temperature (PC2). However, at the lineage level, both temperature (BIO 4) and precipitation (BIO 18) influenced the divergence of CEC lineage (Table 2).…”
Section: Discussionsupporting
confidence: 87%
“…The explanatory power of winter temperature on species with tropical affinity is higher than for those with temperate affinity (Wang et al, ). Previous studies on Quercus have also found that the effect of environmental energy on the species richness of different groups depends on their ancestral niches; environmental energy limits species richness of tropical lineages at high latitudes but of temperate groups at both low and high latitudes (Xu et al, ). Here, we found stronger phylogenetic conservatism in the climatic niches represented by energy, water and seasonality variables for the temperate groups Quercus and Lobatae and the entire genus than for tropical group Cyclobalanopsis .…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether the species richness–climate relationship is mediated by climatic niche conservatism, as suggested by Xu et al (), we reconstructed ancestral climatic niches and estimated the phylogenetic niche conservatism for each species group present on the same continent. A consensus supertree of Quercus was built by merging two recently published Quercus phylogenies (Deng et al, ; Hipp et al, ) based on RAD sequences.…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Global herbaceous floras show an accelerated speciation within a relatively recent history due to their shorter generation time than woody species (Linder 2008, Smith and Donoghue 2008, Hughes and Atchison 2015. Most previous studies on plant richness patterns are focused on woody species (Svenning and Skov 2007, Wang et al 2012b, Xu et al 2013. Many studies focusing on herb-dominated vegetation types (e.g.…”
Section: Introductionmentioning
confidence: 99%